Brucellosis in Camels and Humans: Seroprevalence and Associated Risk Factors in Amibara District of Afar Region, Ethiopia. (28th November 2021) - Wegi, Fekadu Gutema; Amenu, Kebede; Chalchisa, Adugna; Mamo, Gezahegne
Abstract : Brucellosis is an important neglected zoonotic disease caused by infection with bacteria of the genus Brucella affecting different mammalian species including humans. A cross-sectional study was conducted to estimate the seroprevalence of brucellosis in camels and humans and its associated risk factors in Amibara District of Afar Region in Northeast Ethiopia, from October 2019 to May 2020. A total of 250 camel and 120 human sera were serially tested using the Rose Bengal plate test (RBPT) and complement fixation test (CFT). The overall seroprevalence of camel brucellosis in this study was 7.6% (95% CI: 4.9–11.56) by RBPT and 3.2% (95% CI: 1.63–6.2) by combined RBPT and CFT. In humans, twelve (10%) of the collected sera were positive by RBPT among which only four of them (3.33%) were positive by CFT. The risk factor analysis indicated that age, body condition, number of parity, and abortion history were significantly associated with Brucella seropositivity in camel (P ≤ 0.05). In humans, occupation and nonprotective handling of dystocia cases showed an apparent association with Brucella seropositivity. The results of this study indicated that brucellosis is a common health problem in camels and humans in Amibara District of Afar Region. The public health importance of this disease is associated with raw milk consumption and close contact with the animals having history of recent abortion. Therefore, controlling the risk factors, establishing Brucella diagnostic service in human clinics and hospitals, continuous social training with feedback assessments, and overall implementing of One Health approach framework to attain optimal health for people and domestic animals in area are recommended to safeguard the health of society.